Pengaruh Pendidikan dan Pelatihan Serta Kompensasi melalui Motivasi terhadap Kinerja ASN di Kantor Kementerian Agama Kabupaten Tanjung Jabung Barat - Alhudhori, M.; Adriani, Evi (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of education, training, and compensation on the performance of State Civil Apparatus (CSA) with work motivation as an intervening variable at the Ministry of Religious Affairs Office, West Tanjung Jabung Regency. The research method used is a quantitative approach with path analysis. Data were collected through distributing questionnaires to 76 respondents who are active SCA in the Ministry of Religious Affairs Office, West Tanjung Jabung Regency. The results show that education, training, and compensation have a positive and significant effect on the motivation and performance of SCA at the Ministry of Religious Affairs Office, West Tanjung Jabung Regency. However, the motivation variable is unable to strengthen or weaken the influence of the education, training, and compensation variables on SCA performance at the Ministry of Religious Affairs Office, West Tanjung Jabung Regency.